Transparent conductive film

By using a thin substrate with excellent mechanical characteristics and conductivity and a first transparent conductive layer in the transparent conductive film, the problems of easy breakage and visual identification of the film when bending in the prior art are solved, and excellent conductivity and mechanical strength under bending conditions are achieved.

CN116133842BActive Publication Date: 2025-02-28NITTO DENKO CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202180059017.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-07-28
Filing Date
2021-07-21
Publication Date
2025-02-28
Estimated Expiration
2041-07-21

AI Technical Summary

Technical Problem

The existing transparent conductive films are prone to cracks and damage when bending, and the mechanical characteristics of the substrate are insufficient, resulting in visual identification problems in large image display devices.

Method used

A transparent conductive film with excellent mechanical characteristics and conductivity is adopted, which consists of a thin substrate and a first transparent conductive layer on at least one surface. The first transparent conductive layer keeps the resistance value increase rate below 20% when bending, and improves the conductivity and mechanical strength by including metal nanowires and polymer matrix.

Benefits of technology

It realizes excellent conductivity and mechanical strength under bending conditions, avoids film damage and visual recognition problems, and is suitable for large image display devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116133842B_ABST
    Figure CN116133842B_ABST
Patent Text Reader

Abstract

Provided is a transparent conductive film having a substrate and a transparent conductive layer, which has excellent mechanical properties even when the substrate is thin and can exhibit excellent conductivity. The transparent conductive film of the present invention includes: a substrate, and a first transparent conductive layer disposed on at least one surface of the substrate. When the first transparent conductive layer is on the outer side with respect to the substrate and bent 180° with a bending radius R (mm), when the relationship between the bending radius R (mm) and the thickness T (mm) of the substrate is in the range of 0 < T / (2R + T) ≤ 0.07, the resistance value increase rate a caused by the bending is 20% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a transparent conductive film. Background Art

[0002] Conventionally, as a transparent conductive film used for electrodes of a contact sensor or the like, a transparent conductive film having a metal oxide layer such as an indium-tin composite oxide layer (ITO layer) formed on a substrate is mostly used. For such a transparent conductive film, a polyethylene terephthalate film is sometimes used as the substrate, and one of the reasons is that it is advantageous for mechanical properties. However, since the polyethylene terephthalate film has a retardation, when the transparent conductive film using this film is used for a large image display device, problems such as unnecessary coloring of the visually recognized image and appearance of an iris pattern occur. As a substrate with less influence of retardation, a film formed of a cycloolefin resin can be cited. However, the cycloolefin resin film has problems of poor mechanical properties and easy breakage when forming a metal oxide layer.

[0003] In addition, the metal oxide layer such as the ITO layer has a problem of being easily broken due to cracks caused by stress. For example, when the metal oxide layer is on the outside and the transparent conductive film is bent, cracks sometimes occur in the metal oxide layer. As one of the means to prevent this phenomenon, thinning the substrate can be cited. However, in the case of using a cycloolefin resin film as the substrate, if the film (substrate) is thinned, the above-mentioned problem of easy breakage becomes significant.

[0004] Prior Art Documents

[0005] Patent Documents

[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 2009-505358 Summary of the Invention

[0007] Problems to be Solved by the Invention

[0008] The present invention has been made to solve the above problems, and an object thereof is to provide a transparent conductive film having a substrate and a transparent conductive layer, which has excellent mechanical properties even when the substrate is thin and can exhibit excellent conductivity.

[0009] Means for Solving the Problems

[0010] The transparent conductive film of the present invention includes: a substrate, and a first transparent conductive layer disposed on at least one surface of the substrate. When the first transparent conductive layer is on the outside with respect to the substrate and bent 180° with a bending radius R (mm), when the relationship between the bending radius R (mm) and the thickness T (mm) of the substrate is in the range of 0 < T / (2R + T) ≤ 0.07, the increase rate a of the resistance value (surface resistance value) caused by the bending is 20% or less.

[0011] In one embodiment, the transparent conductive film further includes a second transparent conductive layer, and the second transparent conductive layer is disposed on the side of the substrate opposite to the first transparent conductive layer.

[0012] In one embodiment, the first transparent conductive layer includes metal nanowires.

[0013] In one embodiment, the first transparent conductive layer further includes a polymer matrix.

[0014] In one embodiment, the tensile strength at break of the substrate is 100 MPa or less.

[0015] In one embodiment, the material constituting the substrate is a cycloolefin-based resin.

[0016] Effects of the Invention

[0017] According to the present invention, a transparent conductive film can be provided, which has a substrate and a transparent conductive layer, and has excellent mechanical properties and can exhibit excellent conductivity even if the substrate is thin. In particular, the transparent conductive film of the present invention has excellent bendability and is advantageous in that it can maintain excellent conductivity even when bent. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a schematic cross-sectional view of a transparent conductive film according to one embodiment of the present invention.

[0019] Figure 2 It is a schematic cross-sectional view of a transparent conductive film according to another embodiment of the present invention. DETAILED DESCRIPTION

[0020] A. Overall composition of transparent conductive film

[0021] Figure 1 1 is a schematic cross-sectional view of a transparent conductive film according to one embodiment of the present invention. The transparent conductive film 100 includes a substrate 10 and a first transparent conductive layer 20 disposed on one surface of the substrate 10. Although not shown, the transparent conductive film may further include any other appropriate layer.

[0022] When the above-mentioned transparent conductive film is bent 180° with the first transparent conductive layer on the outside compared to the substrate at a bending radius of R (mm), when the relationship between the bending radius R (mm) and the thickness T (mm) of the substrate is in the range of 0 < T / (2R + T) ≤ 0.07, the rising rate a of the resistance value (the surface resistance value measured on the side of the first transparent conductive layer) caused by this bending is 20% or less. Such a transparent conductive film has excellent bendability and can maintain excellent conductivity even when bent. In the transparent conductive film of the present invention, even when using a thin and low-mechanical-strength substrate, the above effects can be obtained, which is advantageous in this regard. Such a transparent conductive film can be obtained, for example, by forming the first transparent conductive layer from metal nanowires or a metal mesh. The rising rate a of the resistance value is preferably 15% or less, more preferably 10% or less. The smaller the rising rate a of the resistance value, the more preferable it is, and its lower limit is, for example, 3% (more preferably 1%, further preferably 0.5%).

[0023] In one embodiment, as Figure 2 shown, the transparent conductive film 100’ may further include a second transparent conductive layer 30. The second transparent conductive layer 30 may be disposed on the side of the substrate 20 opposite to the first transparent conductive layer 10.

[0024] The surface resistance value on the side of the first transparent conductive layer of the transparent conductive film of the present invention is preferably 0.01 Ω / sq to 1000 Ω / sq, more preferably 0.1 Ω / sq to 500 Ω / sq, particularly preferably 0.1 Ω / sq to 300 Ω / sq, and most preferably 0.1 Ω / sq to 100 Ω / sq.

[0025] The surface resistance value on the side of the second transparent conductive layer of the transparent conductive film of the present invention is preferably 0.01 Ω / sq to 1000 Ω / sq, more preferably 0.1 Ω / sq to 500 Ω / sq, particularly preferably 0.1 Ω / sq to 300 Ω / sq, and most preferably 0.1 Ω / sq to 100 Ω / sq.

[0026] The haze value of the transparent conductive film of the present invention is preferably 1% or less, more preferably 0.7% or less, and further preferably 0.5% or less. The smaller the haze value, the more preferable it is, and its lower limit value is, for example, 0.05%.

[0027] The total light transmittance of the transparent conductive film of the present invention is preferably 80% or more, more preferably 85% or more, and particularly preferably 90% or more.

[0028] The thickness of the transparent conductive film of the present invention is preferably 10 μm to 500 μm, more preferably 15 μm to 300 μm, and further preferably 20 μm to 200 μm.

[0029] B. 1st transparent conductive layer

[0030] The first transparent conductive layer preferably includes metal nanowires or a metal mesh, and more preferably includes a metal mesh.

[0031] The thickness of the first transparent conductive layer is preferably 10 nm to 30 μm.

[0032] The total light transmittance of the first transparent conductive layer is preferably 85% or more, more preferably 90% or more, and even more preferably 95% or more.

[0033] The elastic modulus of the first transparent conductive layer at 23°C obtained by atomic force microscopy (AFM) is preferably 20 GPa to 100 GPa, more preferably 30 GPa to 90 GPa, and further preferably 40 GPa to 90 GPa. In such a range, a transparent conductive film having excellent bendability and not easily damaged can be obtained. The first conductive layer having an elastic modulus in the above range can be obtained, for example, by making the first transparent conductive layer contain a polymer matrix as described later. The method for measuring the elastic modulus is described later.

[0034] (First transparent conductive layer including metal nanowires)

[0035] In one embodiment, when the first transparent conductive layer includes metal nanowires, the first transparent conductive layer may further include a polymer matrix. In this embodiment, the metal nanowires may exist in the polymer matrix. In the first transparent conductive layer composed of the polymer matrix, the metal nanowires are protected by the polymer matrix. As a result, a transparent conductive film can be obtained in which corrosion of the metal nanowires is prevented and durability is improved.

[0036] When the first transparent conductive layer includes metal nanowires, the thickness of the first transparent conductive layer is preferably 10 nm to 1000 nm, more preferably 20 nm to 500 nm. When the first transparent conductive layer includes a polymer matrix, the thickness of the first transparent conductive layer corresponds to the thickness of the polymer matrix.

[0037] In one embodiment, the first transparent conductive layer is patterned. As a patterning method, any appropriate method can be used according to the form of the first transparent conductive layer. The shape of the pattern of the first transparent conductive layer can be any appropriate shape according to the purpose. For example, the patterns described in Japanese Unexamined Patent Publication No. 2011-511357, Japanese Unexamined Patent Publication No. 2010-164938, Japanese Unexamined Patent Publication No. 2008-310550, Japanese Unexamined Patent Publication No. 2003-511799, and Japanese Unexamined Patent Publication No. 2010-541109 can be cited. After the first transparent conductive layer is formed on the substrate, it can be patterned using any appropriate method according to the form of the first transparent conductive layer.

[0038] The metal nanowires are conductive materials made of metal, shaped like needles or wires, and having a diameter of nanometers. The metal nanowires may be straight or curved. If the first transparent conductive layer composed of metal nanowires is used, the metal nanowires become a mesh, thereby forming a good conductive path even with a small amount of metal nanowires, and obtaining a transparent conductive film with low resistance.

[0039] The ratio of the thickness d to the length L of the above-mentioned metal nanowires (aspect ratio: L / d) is preferably 10 to 100,000, more preferably 50 to 100,000, and particularly preferably 100 to 10,000. If a metal nanowire with a large aspect ratio like this is used, the metal nanowires are well crossed, and a small amount of metal nanowires can exhibit high conductivity. As a result, a transparent conductive film with high light transmittance can be obtained. It should be noted that in this specification, the "thickness of the metal nanowire" refers to its diameter when the cross-section of the metal nanowire is circular, refers to its short diameter when it is elliptical, and refers to the longest diagonal when it is polygonal. The thickness and length of the metal nanowire can be confirmed by a scanning electron microscope or a transmission electron microscope.

[0040] The thickness of the metal nanowires is preferably less than 500 nm, more preferably less than 200 nm, particularly preferably 10 nm to 100 nm, and most preferably 10 nm to 60 nm. Within such a range, a first transparent conductive layer having high light transmittance can be formed.

[0041] The length of the metal nanowires is preferably 1 μm to 1000 μm, more preferably 1 μm to 500 μm, and particularly preferably 1 μm to 100 μm. When the length is within this range, a transparent conductive film having high conductivity can be obtained.

[0042] As the metal constituting the above-mentioned metal nanowire, any appropriate metal can be used as long as it is a metal with high conductivity. As the metal constituting the above-mentioned metal nanowire, for example, silver, gold, copper, nickel, etc. can be cited. In addition, materials obtained by plating these metals (for example, gold plating) can also be used. The metal nanowire is preferably composed of one or more metals selected from the group consisting of gold, platinum, silver and copper.

[0043] As a method for producing the above-mentioned metal nanowires, any appropriate method may be adopted. For example, there may be mentioned: a method of reducing silver nitrate in a solution; a method of applying a voltage or a current from the tip of a probe to the surface of a precursor, and extracting a metal nanowire from the tip of the probe to continuously form the metal nanowire, etc. In the method of reducing silver nitrate in a solution, silver salts such as silver nitrate are subjected to liquid phase reduction in the presence of a polyol such as ethylene glycol and polyvinyl pyrrolidone, thereby synthesizing silver nanowires. Silver nanowires of uniform size can be mass-produced according to the methods described in, for example, Xia, Y. et al., Chem. Mater. (2002), 14, 4736-4745, Xia, Y. et al., Nanoletters (2003) 3 (7), 955-960.

[0044] The content of the metal nanowires in the first transparent conductive layer is preferably 30 to 100 wt %, more preferably 30 to 90 wt %, and further preferably 45 to 80 wt %, relative to the total weight of the first transparent conductive layer. Within such a range, a transparent conductive film having excellent conductivity and light transmittance can be obtained.

[0045] As the polymer constituting the above-mentioned polymer matrix, any appropriate polymer can be used. As the polymer, for example, acrylic polymers; polyester polymers such as polyethylene terephthalate; aromatic polymers such as polystyrene, polyvinyl toluene, polyvinyl xylene, polyimide, polyamide, polyamide-imide, etc.; polyurethane polymers; epoxy polymers; polyolefin polymers; acrylonitrile-butadiene-styrene copolymer (ABS); cellulose; silicon polymers; polyvinyl chloride; polyacetate; polynorbornene; synthetic rubber; fluorine polymers, etc. It is preferred to use a curable resin (preferably an ultraviolet curable resin) composed of multifunctional acrylates such as pentaerythritol triacrylate (PETA), neopentyl glycol diacrylate (NPGDA), dipentaerythritol hexaacrylate (DPHA), dipentaerythritol pentaacrylate (DPPA), and trimethylolpropane triacrylate (TMPTA).

[0046] When the first transparent conductive layer is composed of a polymer matrix and the metal nanowires are silver nanowires, the density of the first transparent conductive layer is preferably 1.3 g / cm 3 ~10.5g / cm 3 , more preferably 1.5 g / cm 3 ~3.0g / cm 3 When the content is within such a range, a transparent conductive film having excellent conductivity and light transmittance can be obtained.

[0047] When the first transparent conductive layer is composed of a polymer matrix, the elastic modulus of the polymer matrix at 23° C. obtained by an atomic force microscope (AFM) is preferably 20 GPa to 100 GPa, more preferably 30 GPa to 90 GPa, and even more preferably 40 GPa to 90 GPa.

[0048] The first transparent conductive layer can be formed by applying a first conductive layer-forming composition containing metal nanowires on a substrate (or a laminate of a substrate and other layers), and then drying the applied layer.

[0049] In addition to the metal nanowires, the composition for forming the first conductive layer may also contain any appropriate solvent. The composition for forming the first conductive layer may be prepared in the form of a dispersion of metal nanowires. Examples of the solvent include water, alcohol solvents, ketone solvents, ether solvents, hydrocarbon solvents, aromatic solvents, and the like. From the viewpoint of reducing the environmental burden, water is preferably used. The composition for forming the first conductive layer may also contain any appropriate additives according to the purpose. Examples of the additives include anti-corrosion materials for preventing corrosion of metal nanowires, surfactants for preventing aggregation of metal nanowires, and the like. The type, number, and amount of the additives used may be appropriately set according to the purpose.

[0050] When the first transparent conductive layer comprises a polymer matrix, the polymer matrix can be formed by applying a first conductive layer-forming composition as described above and drying it, then applying a polymer solution (polymer composition, monomer composition) on the layer composed of metal nanowires, and then drying or curing the applied layer of the polymer solution. Alternatively, the first transparent conductive layer can be formed using a first conductive layer-forming composition containing a polymer constituting a polymer matrix.

[0051] The dispersion concentration of the metal nanowires in the first conductive layer-forming composition is preferably 0.1 wt % to 1 wt %. Within this range, a first transparent conductive layer having excellent conductivity and light transmittance can be formed.

[0052] As a coating method for the composition for forming the first conductive layer, any appropriate method can be used. As a coating method, for example, a spin coater, a rod coater, a roll coater, a die coater, an inkjet coater, a screen coater, a dip coater, a relief printing method, a gravure printing method, a gravure printing method, etc. can be cited. As a drying method for the coating layer, any appropriate drying method (for example, natural drying, air drying, heating drying) can be used. For example, in the case of heating drying, the drying temperature is representatively 50°C to 200°C, preferably 80°C to 150°C. The drying time is representatively 1 to 10 minutes.

[0053] The polymer solution contains the polymer constituting the polymer matrix or a precursor of the polymer (a monomer constituting the polymer).

[0054] The polymer solution may contain a solvent. Examples of the solvent contained in the polymer solution include alcoholic solvents, ketone solvents, tetrahydrofuran, hydrocarbon solvents, and aromatic solvents. The solvent is preferably volatile. The boiling point of the solvent is preferably 200° C. or less, more preferably 150° C. or less, and further preferably 100° C. or less.

[0055] (First transparent conductive layer including metal mesh)

[0056] The first transparent conductive layer comprising a metal mesh is formed by forming metal fine wires into a grid-like pattern on the above-mentioned substrate. The first transparent conductive layer comprising a metal mesh can be formed by any appropriate method. The first transparent conductive layer can be obtained, for example, as follows: a photosensitive composition (composition for forming a transparent conductive layer) comprising a silver salt is applied to the above-mentioned laminate, followed by exposure treatment and development treatment to form the metal fine wires into a prescribed pattern, thereby obtaining. In addition, the first transparent conductive layer can also be obtained by printing a paste (composition for forming a transparent conductive layer) comprising metal particles into a prescribed pattern. The details of this first transparent conductive layer and its formation method are described, for example, in Japanese Patent Publication No. 2012-18634, and its description is cited in the specification as a reference. In addition, as another example of a transparent conductive layer composed of a metal mesh and its formation method, the transparent conductive layer and its formation method described in Japanese Patent Publication No. 2003-331654 can be cited.

[0057] When the first transparent conductive layer includes a metal mesh, the thickness of the first transparent conductive layer is preferably 0.1 μm to 30 μm, more preferably 0.1 μm to 9 μm, and even more preferably 1 μm to 3 μm.

[0058] (Metallic first transparent conductive layer)

[0059] The transparent conductive layer may be a metal system, more specifically, a layer comprising a metal film or a layer comprising an oxide metal film. As materials constituting such a transparent conductive layer, for example, metals such as Cu, Al, Fe, Cr, Ti, Si, Nb, In, Zn, Sn, Au, Ag, Co, Cr, Ni, Pb, Pd, Pt, W, Zr, Ta, Hf, Mo, Mn, Mg, and V are preferably used. In addition, materials containing two or more of these metals, alloys containing these metals as main components, oxides, etc. may also be used. For example, indium-tin composite oxide (ITO) may be used.

[0060] When the first transparent conductive layer is made of a metal, the thickness of the first transparent conductive layer is 10 nm to 400 nm, more preferably 50 nm to 350 nm, and particularly preferably 100 nm to 200 nm.

[0061] The metal-based first transparent conductive layer can be formed by any appropriate method, for example, by vacuum film forming methods such as sputtering, chemical vapor deposition (CVD), physical vapor deposition (PVD), ion plating, plating (electroplating, chemical plating), hot stamping, coating, etc.

[0062] When the first transparent conductive layer is a metal-based layer, a protective layer may be formed on the first transparent conductive layer (on the surface opposite to the substrate). As a material for forming the protective layer, for example, one or more metals selected from Ni, Cu, Ti, Si, Zn, Sn, Cr, Fe, indium, gallium, antimony, zirconium, magnesium, aluminum, gold, silver, palladium, and tungsten or their oxides may be used. The thickness of the protective layer is, for example, 1 nm to 50 nm.

[0063] In one embodiment, the first transparent conductive layer may be patterned into a predetermined pattern. The shape of the pattern of the transparent conductive layer is not particularly limited as long as it is a pattern that works well as a touch panel (e.g., a capacitive touch panel), and for example, patterns described in Japanese Unexamined Patent Publication No. 2011-511357, Japanese Unexamined Patent Publication No. 2010-164938, Japanese Unexamined Patent Publication No. 2008-310550, Japanese Unexamined Patent Publication No. 2003-511799, and Japanese Unexamined Patent Publication No. 2010-541109 may be cited. The first transparent conductive layer may be patterned using a known method after being formed on the substrate.

[0064] C. Base material

[0065] The above-mentioned substrate is typically composed of any appropriate resin. As the resin constituting the above-mentioned substrate, for example, cycloolefin resin, polyimide resin, polyvinylidene chloride resin, polyvinyl chloride resin, polyethylene terephthalate resin, polyethylene naphthalate resin, etc. can be cited. Preferably, cycloolefin resin is used. If a substrate composed of cycloolefin resin is used, a transparent conductive film with excellent bendability can be obtained. In addition, it is also advantageous from the viewpoint of optical properties. In the present invention, even if a substrate with low fracture strength such as cycloolefin film is used, a transparent conductive film that is not easily damaged can be provided.

[0066] As the above-mentioned cycloolefin resin, for example, polynorbornene can be preferably used. Polynorbornene refers to a (co)polymer obtained by using a part or all of a norbornene monomer having a norbornene ring as the starting material (monomer). As the above-mentioned polynorbornene, various products are commercially available. As specific examples, the trade names "Zeonex" and "Zeonor" manufactured by Zeon Corporation, the trade name "Arton" manufactured by JSR Corporation, the trade name "Topas" manufactured by TICONA Corporation, and the trade name "APEL" manufactured by Mitsui Chemicals, Inc. can be cited.

[0067] The glass transition temperature of the resin constituting the substrate is preferably 50 to 200° C., more preferably 60 to 180° C., and further preferably 70 to 160° C. A substrate having a glass transition temperature within such a range can prevent degradation during formation of the first transparent conductive layer.

[0068] The thickness of the substrate is preferably 8 μm to 150 μm, more preferably 10 μm to 120 μm, further preferably 10 μm to 100 μm, and particularly preferably 15 μm to 80 μm. In the present invention, even if a thin substrate is used, a transparent conductive film that is not easily damaged can be provided. By using a thin substrate, a transparent conductive layer (especially the first transparent conductive layer) is not easily damaged even when bent, and a transparent conductive film that can maintain excellent conductivity can be obtained.

[0069] In one embodiment, the tensile rupture strength of the substrate is 100 MPa or less. In another embodiment, the tensile rupture strength of the substrate is 80 MPa or less. In the present invention, even if a substrate with a relatively small rupture strength is used, a transparent conductive film that is not easily damaged can be provided. The lower limit of the tensile rupture strength of the substrate is, for example, 30 MPa (preferably 40 MPa). It should be noted that the tensile rupture strength can be measured at room temperature (23°C) in accordance with JIS K 7161.

[0070] The total light transmittance of the substrate is preferably 80% or more, more preferably 85% or more, and particularly preferably 90% or more. Within such a range, a transparent conductive film suitable as a transparent conductive film provided in a touch panel or the like can be obtained.

[0071] The substrate may further include any appropriate additive as required. Specific examples of additives include plasticizers, heat stabilizers, light stabilizers, lubricants, antioxidants, ultraviolet light absorbers, flame retardants, colorants, antistatic agents, solubilizers, crosslinking agents, and thickeners. The type and amount of the additive used may be appropriately set according to the purpose.

[0072] As required, various surface treatments can be performed on the above-mentioned substrate. The surface treatment adopts any appropriate method according to the purpose. For example, low-pressure plasma treatment, ultraviolet irradiation treatment, corona treatment, flame treatment, acid or alkali treatment can be mentioned. In one embodiment, the substrate is surface treated to make the substrate surface hydrophilic. If the substrate is hydrophilic, the processability when applying the transparent conductive layer forming composition prepared by an aqueous solvent is excellent. In addition, a transparent conductive film with excellent adhesion between the substrate and the transparent conductive layer can be obtained.

[0073] D. Second transparent conductive layer

[0074] The second transparent conductive layer may be of any appropriate composition as long as it has conductivity. In one embodiment, the second transparent conductive layer may adopt the composition described in item B. In another embodiment, the second transparent conductive layer is composed of a metal oxide. As the metal oxide, for example, indium oxide, tin oxide, zinc oxide, indium-tin composite oxide, tin-antimony composite oxide, zinc-aluminum composite oxide, indium-zinc composite oxide, etc. may be cited. Among them, indium-tin composite oxide (ITO) is preferred. The metal oxide may be a crystallized metal oxide. As described later, the crystallized metal oxide refers to a metal oxide obtained by heating (for example, heating at 120°C to 200°C) after forming a metal oxide film.

[0075] As a method for forming the second transparent conductive layer composed of a metal oxide, for example, a method of forming a metal oxide layer by any appropriate film-forming method (for example, vacuum evaporation method, sputtering method, CVD method, ion plating method, spraying method, etc.) to obtain the second transparent conductive layer can be cited. The metal oxide layer can be directly used as the second transparent conductive layer, or it can be further heated to crystallize the metal oxide. The temperature during the heating is, for example, 120° C. to 200° C.

[0076] The total light transmittance of the second transparent conductive layer is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more.

[0077] The thickness of the second transparent conductive layer is preferably 50 nm or less, more preferably 40 nm or less. Within this range, a transparent conductive film with excellent light transmittance can be obtained. The lower limit of the thickness of the conductive layer is preferably 1 nm, more preferably 5 nm.

[0078] Example

[0079] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples. Evaluation methods in the examples and comparative examples are as follows.

[0080] (1) Conductivity after bending

[0081] The resistance value of the transparent conductive film after bending was measured.

[0082] Ag paste was applied to both ends of the first conductive layer of a transparent conductive film (length 100 mm × width 20 mm) in the longitudinal direction to obtain a test piece. The test piece was hung on a stainless steel round bar (radius: R mm) with the first conductive layer on the outside, and bent 180° along the round bar in the longitudinal direction. Then, weights (500 g each) were hung at both ends in the longitudinal direction by a fixture, and kept in this state for 10 seconds.

[0083] After the above operation, the weight and the fixture are removed, and the surface resistance value between the Ag paste parts (resistance value after bending) is confirmed by a tester. When the increase rate of the surface resistance value relative to the surface resistance value before bending is less than 20%, it is considered to be conductive. When the increase rate exceeds 20%, it is considered to be conductive.

[0084] (2) Elastic modulus

[0085] The transparent conductive film was fixed on a specified sample stand, and the first transparent conductive layer was subjected to contact resonance measurement using AFM (MEP-3D-SA, manufactured by Oxford Instruments). After the measurement, the elastic modulus was calculated. It should be noted that when calculating the elastic modulus, a silicon wafer (assuming an elastic modulus of 1500 GPa) was used as a standard sample. The detailed measurement conditions are described below.

[0086] Device: MEP-3D-SA manufactured by Oxford Instruments

[0087] Measurement mode: contact resonance method (DART CR)

[0088] Probe: Si (3N / m equivalent)

[0089] Measuring range: 3μm□

[0090] Measuring atmosphere: Atmosphere

[0091] Measuring temperature: room temperature

[0092] [Production Example 1]

[0093] (Manufacturing of Metal Nanowires)

[0094] In a reaction vessel equipped with a stirring device, 5 ml of anhydrous ethylene glycol and an anhydrous ethylene glycol solution of PtCl2 (concentration: 1.5×10 -4mol / L) 0.5 ml. After 4 minutes, 2.5 ml of anhydrous ethylene glycol solution of AgNO3 (concentration: 0.12 mol / l) and 5 ml of anhydrous ethylene glycol solution of polyvinyl pyrrolidone (MW: 55000) (concentration: 0.36 mol / l) were simultaneously added to the obtained solution over 6 minutes. After the addition, the mixture was heated to 160°C and reacted for more than 1 hour until AgNO3 was completely reduced to generate silver nanowires. Next, acetone was added to the reaction mixture containing silver nanowires obtained as described above until the volume of the reaction mixture was 5 times, and the reaction mixture was centrifuged (2000 rpm, 20 minutes) to obtain silver nanowires. The silver nanowires (concentration: 0.2 wt%) and pentaethylene glycol dodecyl ether (concentration: 0.1 wt%) were dispersed in pure water to prepare a silver nanowire dispersion.

[0095] [Example 1]

[0096] (Preparation of Transparent Conductive Layer-Forming Composition (PN))

[0097] 25 parts by weight of the silver nanowire dispersion was diluted with 75 parts by weight of pure water to prepare a transparent conductive layer-forming composition (PN) having a solid content concentration of 0.05% by weight.

[0098] (Preparation of Monomer Composition)

[0099] 1 part by weight of pentaerythritol triacrylate (trade name "Viscoat#300" manufactured by Osaka Organic Chemical Industry Co., Ltd.) and 0.2 part by weight of a photopolymerization initiator (trade name "Irgacure 907" manufactured by BASF) were diluted with 80 parts by weight of isopropyl alcohol and 19 parts by weight of diacetone alcohol to obtain a monomer composition having a solid content concentration of 1% by weight.

[0100] (Production of Transparent Conductive Film)

[0101] The transparent conductive layer-forming composition (PN) was applied as a first transparent conductive layer-forming composition on one side of a substrate (cycloolefin film (manufactured by Zeon Corporation, trade name "ZEONOR (registered trademark)", thickness 55 μm) and dried. Furthermore, the monomer composition was applied on the first transparent conductive layer-forming composition (PN) coating layer and dried at 90° C. for 1 minute. Thereafter, a 300 mJ / cm 2 The first transparent conductive layer is formed by ultraviolet irradiation.

[0102] A transparent conductive film was obtained as described above. The obtained transparent conductive film was subjected to the above-mentioned evaluations (1) and (2). The radius of the round bar used in the evaluation (1) was set to 1 mm (diameter: 2 mm). The results are shown in Table 1.

[0103] [Example 2]

[0104] A transparent conductive film was obtained in the same manner as in Example 1. The obtained transparent conductive film was subjected to the above-mentioned evaluations (1) and (2). The radius of the round rod used in the evaluation (1) was set to 0.5 mm (diameter: 1 mm). The results are shown in Table 1.

[0105] [Example 3]

[0106] A transparent conductive film was obtained in the same manner as in Example 1 except that a substrate (cycloolefin film (manufactured by Zeon Corporation, trade name "ZEONOR (registered trademark)", thickness 55 μm) was used instead of the substrate (cycloolefin film (manufactured by Zeon Corporation, trade name "ZEONOR (registered trademark)", thickness 100 μm). The obtained transparent conductive film was subjected to the above-mentioned evaluations (1) and (2). The radius of the round rod used in the evaluation (1) was set to 1 mm (diameter: 2 mm). The results are shown in Table 1.

[0107] [Comparative Example 1]

[0108] A transparent conductive layer (thickness: 30 nm) composed of an indium-tin oxide layer was formed on one surface of a substrate (cycloolefin film (manufactured by Zeon Corporation, trade name "ZEONOR (registered trademark)", thickness 55 μm) by sputtering to obtain a transparent conductive film.

[0109] The obtained transparent conductive film was subjected to the above-mentioned evaluations (1) and (2). The radius of the round bar used in the evaluation (1) was set to 1 mm (diameter: 2 mm). The results are shown in Table 1.

[0110] [Comparative Example 2]

[0111] A transparent conductive film was obtained in the same manner as in Comparative Example 1 except that a substrate (cycloolefin film (manufactured by Zeon Corporation, trade name "ZEONOR (registered trademark)", thickness 55 μm) was used instead of the substrate (cycloolefin film (manufactured by Zeon Corporation, trade name "ZEONOR (registered trademark)", thickness 100 μm). The obtained transparent conductive film was subjected to the above-mentioned evaluations (1) and (2). The radius of the round rod used in the evaluation (1) was set to 1 mm (diameter: 2 mm). The results are shown in Table 1.

[0112] [Table 1]

[0113]

[0114] As is clear from Table 1, the transparent conductive film has excellent bendability and can maintain excellent conductivity when bent under specific conditions.

[0115] Description of Reference Numerals

[0116] 10. Base material

[0117] 201st transparent conductive layer

[0118] 30 2nd transparent conductive layer

[0119] 100, 100' transparent conductive film

Claims

1. A transparent conductive film, comprising: a substrate, and a first transparent conductive layer disposed on at least one surface of the substrate, when the first transparent conductive layer is on the outer side with respect to the substrate and is bent 180° with a bending radius R (mm), when the relationship between the bending radius R (mm) and the thickness T (mm) of the substrate is in the range of 0 < T / (2R + T) ≤ 0.07, the resistance value increase rate a caused by the bending is 20% or less, the bending radius R is 0.5 mm, the first transparent conductive layer contains metal nanowires and a polymer matrix, the elastic modulus of the first transparent conductive layer at 23°C obtained by atomic force microscopy (AFM) is 20 GPa to 100 GPa, the first transparent conductive layer is formed as follows: a first conductive layer forming composition containing metal nanowires is coated on the substrate, and then the coated layer is dried. A monomer composition is coated on the layer composed of metal nanowires, and then the coated layer of the monomer composition is dried or cured to form a polymer matrix.

2. The transparent conductive film according to claim 1, further comprising a second transparent conductive layer, and the second transparent conductive layer is disposed on the side of the substrate opposite to the first transparent conductive layer.

3. The transparent conductive film according to claim 1 or 2, wherein: The tensile fracture strength of the substrate is 100 MPa or less.

4. The transparent conductive film according to any one of claims 1 to 3, wherein The material constituting the substrate is a cycloolefin resin.

Citation Information

Patent Citations

  • Conductive film and method of manufacturing same

    JP2003331654A

  • A flexible and transparent contact detection system for electronic devices

    JP2003511799A

  • Capacitance input device

    JP2008310550A

  • Transparent conductors based on nanowires

    JP2009505358A

  • Touch screen panel

    JP2010164938A